2019
DOI: 10.1017/s1049023x19004989
|View full text |Cite
|
Sign up to set email alerts
|

The Physical and Mental Health Challenges Experienced by 9/11 First Responders and Recovery Workers: A Review of the Literature

Abstract: Introduction:In the years following the September 11, 2001 terrorist attacks in New York (USA), otherwise known as 9/11, first responders and recovery workers began experiencing a range of physical and mental health challenges. Publications documenting these provide an important evidence-base identifying exposure-related health challenges associated with environmental exposures from the World Trade Center (WTC) site and describe the key lessons learned regarding both physical and mental health challenges (incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 65 publications
0
19
1
Order By: Relevance
“…Medical workers are at high risk of exposure to COVID-19 as compared to non-medical workers and are faced with high levels of stress [ 31 , 32 ]. Studies have shown that in major public health emergencies, health workers are the main responders to outbreaks and that they are often left with more lasting and more complex psychological damage [ 33 , 34 ]. In our study, we found that compared to the outbreak stage, the stable stage of the epidemic had a significantly higher psychological impact in medical workers than in non-medical workers.…”
Section: Discussionmentioning
confidence: 99%
“…Medical workers are at high risk of exposure to COVID-19 as compared to non-medical workers and are faced with high levels of stress [ 31 , 32 ]. Studies have shown that in major public health emergencies, health workers are the main responders to outbreaks and that they are often left with more lasting and more complex psychological damage [ 33 , 34 ]. In our study, we found that compared to the outbreak stage, the stable stage of the epidemic had a significantly higher psychological impact in medical workers than in non-medical workers.…”
Section: Discussionmentioning
confidence: 99%
“…The literature has extensively documented the psychological and emotional health disruptions caused by major stressful events on individuals (Ghodse and Galea 2006 ; Smith et al 2019 ). Primarily, the researchers and scientists have focused on preventing the transmission of COVID-19 and vaccine discovery (Rathod et al 2020 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In the last decades, a wide body of research has evidenced the disrupting role that major stressful events play on psychological and emotional health, even when individuals are not directly exposed to stressful events [14][15][16]. Studies conducted during the main outbreaks from SARS [17] to the Middle East respiratory syndrome (MERS) [18], and currently COVID-19, showed that front-line medical staff reports high levels of stress that result in depression, anxiety, and post-traumatic stress disorder (PTSD) due to the outbreaks [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%